FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR SISWA SMA AL-HIKMAH PULO GADUNG, JAKARTA TIMUR SELAMA PANDEMI COVID-19 - Halim Rasyid; Sukardi; Endang Tri Pujiastuti (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
The purpose of this research is to find out what factors influence the learning motivation of students at AlHikmah Pulo Gadung High School, East Jakarta during the pandemic period, and to determine which factors significantly influence learning motivation at Al-Hikmah Pulo Gadung High School, East Jakarta during the pandemic period. This research was conducted by collecting data by distributing questionnaires to students Al-Hikmah Pulo Gadung High School, East Jakarta. The sample is taking by using saturated sampling technique. Data were analyzed using factor analysis and multiple linear regression analysis. The results showed that of the several variables studied there were two factors. These factors are ideals and conditions of students, and students abilities. Of the two factors formed significantly influence the learning motivation at Al-Hikmah Pulo Gadung High School during the pandemic period.